Decollectivist Strategies in Oceania - Peetz, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2002)
SummaryEach action of a decollectivizing employer—be it in the realm of employment practices, information or relational actions—has both real and symbolic dimensions that may be inclusivist, exclusivist or both. While many attempts at decollectivism are crude, Australia has seen the emergence of a coherent model of sophisticated decollectivist behaviour which has policy implications for many countries. Some analogies can be seen between certain sophisticated strategies of decollectivizing employers and state strategies of Oceania in Orwell’s 1984, though there are many limits to such analogies and indeed to the success of decollectivist strategies, due to the contradiction between rhetoric and actions, employees’ exposure to other discourses and the potential for union response and renewal.